A signaling organelle containing the nerve growth factor-activated receptor tyrosine kinase, TrkA - Grimes, Mark L. (The National Academy of Sciences of the USA, 1997)
The topology of signal transduction is particularly important for neurons. Neurotrophic factors such as nerve growth factor (NGF) interact with receptors at distal axons and a signal is transduced by retrograde transport to the cell body to ensure survival of the neuron. We have discovered an organelle that may account for the retrograde transport of the neurotrophin signal. This organelle is derived from endocytosis of the receptor tyrosine kinase for NGF, TrkA. In vitro reactions containing semi-intact PC12 cells and ATP were used to enhance recovery of a novel organelle: small vesicles containing internalized NGF bound to activated TrkA. These vesicles were distinct from clathrin coated vesicles, uncoated primary endocytic vesicles, and synaptic vesicles, and resembled transport vesicles in their sedimentation velocity. They contained 10% of the total bound NGF and almost one-third of the total tyrosine phosphorylated TrkA. These small vesicles are compelling candidates for the organelles through which the neurotrophin signal is conveyed down the axon.